Complete Depolymerization and Repolymerization of a Sugar Poly(orthoester). Issue 24 (24th November 2017) - Li, Lingyao; Maiti, Sampa; Thompson, Nicole A.; Milligan, Ian J.; Du, Wenjun
Abstract: The capability of a polymer to depolymerize, regenerating its original monomer for further polymerization, is very attractive in terms of sustainability. Recently discovered sugar poly(orthoesters) are an important class of glycopolymer. The high sensitivity of the backbone orthoester linkage toward acidolysis provides a valuable model to study the depolymerization. Herein, a sugar poly(orthoester) is shown to be completely depolymerized under acidic conditions. Interestingly, instead of the original monomer, the depolymerization gave a stable cyclic product (1, 6‐anhydro glucopyranose) in most cases, which was kinetically and thermodynamically favored. However, this pathway could be inhibited by chemically deactivating a key intermediate and thus favoring the formation of the original monomer. Efficient repolymerizaton of the regenerated monomer is also demonstrated. Abstract : Candy wrapper : Herein, a sugar poly(orthoester) is shown to be completely and reversibly depolymerized under acidic conditions. Instead of the original monomer, the depolymerization gave stable cyclic product 1, 6‐anhydro glucopyranose in most cases. However, this pathway could be inhibited by chemically deactivating a key intermediate and thus favoring the formation of the original monomer. Efficient repolymerizaton of the regenerated monomer is also demonstrated.